Bystanders of ethnic victimization: Do classroom context and teachers' approach matter for how adolescents intend to act?. Issue 5 (16th July 2022) - Bayram Özdemir, Sevgi; Yanagida, Takuya; Özdemir, Metin
Abstract: The study examined how adolescents' individual characteristics and class context are related to bystander behaviors in cases of ethnic victimization. The sample included 1065 adolescents in Sweden ( M age  = 13.12, SD  = 0.42; 55%males). Female adolescents, adolescents of immigrant background, and adolescents with positive attitudes toward immigrants had greater intentions to defend and comfort victimized peers. Positive inter‐ethnic contact norms in class were positively associated with intention to comfort the victim. Teachers' non‐tolerance of ethnic victimization was positively related to adolescents' intentions to ask the perpetrator to stop and talk to teacher. The effects were the same across adolescents with different attitudes toward immigrants. Findings highlight the importance of class context and teachers in fostering adolescents' prosocial and assertive interventions in bias‐based hostile behaviors.